Two-Stage Continuous Conversion of Carbon Monoxide to Ethylene by Whole Cells of Azotobacter vinelandii - Natzke, Jace (Appl Environ Microbiol, 2020)
Azotobacter vinelandii is an obligate aerobic diazotroph with a verified transient ability to reduce carbon monoxide to ethylene by its vanadium nitrogenase. In this study, we implemented an industrially relevant continuous two-stage stirred-tank system for in vivo biotransformation of a controlled supply of air enriched with 5% carbon monoxide to 302 μg ethylene g(−1) glucose consumed. To attain this value, the process required overcoming critical oxygen limitations during cell proliferation while simultaneously avoiding the A. vinelandii respiratory protection mechanism that negatively impacts in vivo nitrogenase activity. Additionally, process conditions allowed the demonstration of carbon monoxide’s solubility as a reaction-limiting factor and a competitor with dinitrogen for the vanadium nitrogenase active site, implying that excess intracellular carbon monoxide could lead to a cessation of cell proliferation and ethylene formation as shown genetically using a new strain of A. vinelandii deficient in carbon monoxide dehydrogenase. IMPORTANCE Ethylene is an essential commodity feedstock used for the generation of a variety of consumer products, but its generation demands energy-intensive processes and is dependent on nonrenewable substrates. This work describes a continuous biological method for investigating the nitrogenase-mediated carbon monoxide reductive coupling involved in ethylene production using whole cells of Azotobacter vinelandii. If eventually adopted by industry, this technology has the potential to significantly reduce the total energy input required and the ethylene recovery costs, as well as decreasing greenhouse gas emissions associated with current production strategies.